The Political Dimension in the Poems of Uri Tzvi Greenberg הממד הפוליטי בשיריו של אורי-צבי גרינברג (Journal of the College of Languages (JCL), 2018)
אורי-צבי גרינברג, אחד המשוררים היהודים הבולטים במאה ה-20, ולפי מבקרים רבים, היה גרינברג מהמשוררים החלוצים בתקופה שמלאה בחדשנות ובתנודת האירועים הפוליטיים והביטחוניים, באירופה ובמזרח התיכון. גרינברג יליד גליציה ב-1894, גדל במשפחה חסידית, הוא הגר פלסטינה ב-1923, ומשנה ההיא גרינברג נצל את עצמו לעבודה הספרותית והפוליטית ביחד. הוא תרם להקמתם של כתבי-עת והעתונים וכתב יצירות ספרותיות רבות, רובן היו שירים בעלי ממדים פוליטיים בהשפעת רקעו הציוני. גרינברג שר בפלסטין על-אף-פי-שלא נולד שם כמו שאר הסופרים היהודים בתקופה ההיא. אנו יכולים לומר שגרינברג היה מהסופרים שנצלו את יצירותיהם לשירות הציונות ומטרותיה. באמצעות העיון העמוק בשיריו של גרינברג מצאנו שרוב יצירותיו מסתובבות בציר מרכזי, שהוא הקריאה להגירה לפלסטין והקמת (מדינת-ישראל).Abstract Uri Tzvi Greenberg is one of the most prominent Jewish poets of the 20th century. According to many critics, Greenberg was one of the leading poets in a period of uncertainty and volatility in political and security events in Europe and the Middle East. Born in Galicia in 1894, he grew up in a Hassidic family. He immigrated to Palestine in 1923. Since then, he has devoted himself to both literary and political work. He has contributed to the establishment of many periodicals, newspapers and books of many literary products (productions), most of which were poems of political dimensions influenced by his Zionist background. Greenberg sings in Palestine even though he was not born, like many Jewish writers of that period. We can say here that Greenberg was one of the writers who ridiculed their products to serve the Zionism and its objectives. We found through our in-depth research in his poems that most of his products revolve around a central axis: calling for immigration to Palestine and establishing the State of Israel. Key words: Greenberg, The Political Dimension, Products, The Zionism.